Why do financial systems differ? History matters - Cyril Monnet; Erwan Quintin (European Central Bank (ECB), 2005)
We describe a dynamic model of financial intermediation in which fundamental characteristics of the economy imply a unique equilibrium path of bank and financial market lending. Yet we also show that economies whose fundamental characteristics have converged may continue to have very different financial structures. Because setting up financial markets is costly in our model, economies that emphasize financial market lending are more likely to continue doing so in the future, all else equal.
Keywords: L16; G10; G20; N20; 330; banks; convergence; Financial Institutions; financial markets; Financial Systems; Finanzmarkt; Finanzintermediation; Dynamisches Gleichgewicht; Theorie